Medical problems in adult women with Turner's syndrome. - Elsheikh, M; Conway, G; Wass, J (1999)
Turner's syndrome, the most common chromosome abnormality in females, is the consequence of complete absence or partial deletion of one X chromosome. It is associated with a wide spectrum of clinical features of which short stature and gonadal dysgenesis are almost invariably present. Women with Turner's syndrome have a reduced life expectancy primarily as a result of cardiovascular disease. They are also susceptible to a number of other disorders including autoimmune thyroiditis, osteoporosis, renal and gastrointestinal disease. Thus, women with Turner's syndrome should be followed up by a multidisciplinary team of physicians with an interest in the disorder following discharge from paediatric care. This review aims to highlight the problems associated with Turner's syndrome in adulthood and to discuss important management strategies.